Drug development for onchocerciasis-the past, the present and the future - Tagboto, Senyo; Orish, Verner (Frontiers in Tropical Diseases, 2022)
Onchocerciasis affects predominantly rural communities in Africa, and with small foci in South America and the Yemen. The disease is a major cause of blindness and other significant morbidity and mortality. Control programs have achieved a major impact on the incidence and prevalence of onchocerciasis by interrupting transmission with vector control programs, and treatment with mass drug administration using the microfilaricide ivermectin. Over the last few decades, several microfilaricides have been developed. This initially included diethylcarbamazine, which had significant side effects and is no longer used as such. Ivermectin which is a safe and highly effective microfilaricide and moxidectin which is a longer acting microfilaricide are presently recognized therapies. Suramin was the first effective macrofilaricide but was prohibitively toxic. Certain antibiotics including doxycycline can help eliminate adult worms by targeting its endosymbiont bacteria, Wolbachia pipientis. However, the dosing regimens may make this difficult to use as part of a mass disease control program in endemic areas. It is now widely recognized that treatments that are able to kill or permanently sterilize adult filarial worms should help achieve the elimination of this disease. We summarize in detail the historic drug development in onchocerciasis, including prospective future candidate drugs.